Epidemiology and clinical characteristics of behçet's disease in the US: A population‐based study - Calamia, Kenneth T.; Wilson, Floranne C.; Icen, Murat; Crowson, Cynthia S.; Gabriel, Sherine E.; Kremers, Hilal Maradit (Arthritis and rheumatism, 2009)
Objective Behçet's disease (BD) is a rare, multisystem inflammatory disorder of unknown cause. Although well‐documented in Eastern populations, epidemiologic data is scarce in North American countries. Here we describe the incidence and prevalence of BD in Olmsted County, Minnesota over 45 years. Methods We identified an incidence cohort of subjects age ≥18 years who had a clinical diagnosis of and/or fulfilled the International Study Group (ISG) criteria for BD from January 1, 1960 to January 1, 2005. Age‐ and sex‐specific incidence and prevalence were estimated and age‐ and sex‐adjusted to the 2000 US total population. Results The study population was comprised of 13 subjects with BD; 11 fulfilled ISG criteria between 1960 and 2005. Mean ± SD age was 31 ± 9 years, and 69% were white. Point prevalence in 2000 was 5.2 per 100,000 population (95% confidence interval [95% CI] 0.64–9.84). The overall annual age‐ and sex‐adjusted incidence of BD was 0.38 per 100,000 population (95% CI 0.17–0.59), with a higher incidence in women (0.51 per 100,000; 95% CI 0.17–0.84) than in men (0.26 per 100,000; 95% CI 0.004–0.52). Dermatologic lesions included oral ulcers (100%), genital ulcers (62%), erythema nodosum (46%), and papulopustular lesions (54%). Ocular lesions, vascular complications, and central nervous system involvement were present in 8, 3, and 3 subjects, respectively. Conclusion Our study shows an overall incidence of 0.38 per 100,000 population, which is comparable with other Western populations. The prevalence of 5.2 per 100,000 population is similar to estimates reported in Western countries, but lower than that in countries along the Silk Road.